Project-Based Learning (PJBL) in Implementing Entrepreneurial Character and High Level Thinking Skills for Students - Zulfikar, Muhammad Vicky (PT Maju Malaqbi Makkarana, 2024)
This article aims to analyze Project-Based Learning (Pjbl) in Instilling Entrepreneurial Character and High-Level Thinking Skills for Students. The method in this research is the Systematic Literature Review (SLR). Based on the results of the analysis, it was found that Project Based Learning (JBL) can have a positive influence on instilling an entrepreneurial character, although it must take time. The results also show that the Project Based Learning Method (PPA) can have a major influence on students' high-level thinking skills, High Order Thinking Skills are often used by students when it is a transfer of knowledge to lecturers.